Effect of duck hatchery waste supplementation as an alternative protein source on growth performance, and income over feed cost of hybrid ducks - Ghoni, Abdul; Hanif, Muhammad F.; Heru Sasongko; Ariyadi, Bambang (Journal of Advanced Veterinary Research, 2024)
Duck hatchery waste is an alternative feed ingredient for protein sources in poultry. This study aimed to determine the effect of duck hatchery waste supplementation on growth performance, and income over feed cost of hybrid ducks. A total of 120-day-old male hybrid ducks (body weight: 61.4 g ± 4.9) were randomly divided into three treatments (4 replicates per treatment, 10 ducks per replicate). At 0-14 days of age, ducks were fed the same complete feed in all treatments. After 14 days of age, ducks were fed an experimental diet until 35 days of age. The treatment feed consists of a basal diet (P0), basal diet with 8% hatchery waste (P1), and basal diet with 16% hatchery waste (P2). Supplementation of 8% and 16% duck hatchery waste increased accumulated feed consumption and body weight gain of hybrid ducks on day 35 (P<0.05). However, feeding duck hatchery waste did not affect the feed conversion ratio of hybrid ducks on week 5. In contrast, supplementation of duck hatchery waste decreased the FCR of hybrid ducks at weeks 3 and 4. Furthermore, the inclusion of duck hatchery waste in the duck diet increased revenue generation from duck sales and also increased the IOFC value. In conclusion, supplementation of duck hatchery waste can increase feed intake and body weight gain, duck sales and IOFC value of hybrid ducks.